Burning and building : schooling and state formation in Japan, 1750-1890 - Platt, Brian, 1970- (Harvard East Asian monographs, 2004)
"Soon after overthrowing the Tokugawa government in 1868, the new Meiji leaders formulated ambitious plans to build a modern nation-state. Among the earliest and most radical of the Meiji reforms was a plan for a centralized, compulsory educational system, modeled after those in Europe and America. Envisioning a future in which "there shall be no community with an unschooled family, and no family with an unschooled person," Meiji leaders hoped that schools would curb mounting social disorder and mobilize the Japanese against the threat of Western imperialism." "The sweeping tone of this revolutionary plan obscured the fact that the Japanese people already had their own ideas about what a school should be. In the century preceding the Meiji Restoration, communities throughout Japan had established some 50,000 schools with almost no guidance or support from the government. Consequently, the Meiji government's plan for a new and different educational system provoked a vigorous response from local society. Many community leaders bought into the new plan and worked energetically to implement it, while others resented this new intrusion and resisted it fiercely. The ensuing conflicts and compromises fueled the growth of a modern educational system that bore the imprint of local demands and expectations. This book traces the unfolding of this process in Nagano prefecture and explores how local people negotiated the formation of the new order in their communities."--Jacket.